PENATA LAYANAN PERPUSTAKAAN SEKOLAH DASAR (Studi Situs SD Negeri Bonangrejo Demak) - Wiyono, Widiarso (2011)
The objectives of this research are to describe (1) the characteristic of circulation service in Elementary School state Bonangrejo Demak, (2) the characteristic of reference service in Elementary School state Bonangrejo Demak, and (3) The characteristic of guidance service in Elementary School state Bonangrejo Demak. This research is qualitative research with ethnography design. This research is conducted in Elementary School state Bonangrejo Demak. Human resources in this research are principal, library's arranger, and teacher. Data collection method used depth interview, observation, and documentation. Data analysis used arranges analysis in site. Data validity is consist of credibility, transferability, dependability, and conformability The research's result shows that (1) the library gives service from Monday until Saturday according to learning hours at school, while in the Friday is until 13 pm. The system of library service that applied in Elementary School state Bonangrejo Demak used mixed Access service system that is open access and closed access and automatic system. Every people is borrow 2 book maximally with borrowing time 1 week and the limitation of borrow is can be lengthen twice. In return service, the manager made determination to give a sanction according to the violation level that is done. (2) The library has general reference counted 628 exemplar, philosophy and physiology counted 111 exemplars, religion counted 134 exemplars, social science counted 1.459 exemplars, language counted 1.237 exemplars, natural science counted 2.139 exemplars, application science (technology) counted 2.549 exemplars, art and exercise counted 505 exemplars, literature counted 1.278 exemplars, geography and general history counted 265 exemplars. Those data is not included reading books such as magazine, newspaper that change everyday and also clipping. The books is grouped according to knowledge group and arranged in alphabet. (3) The guidance service is done every day after learning hours. Giving guidance between classes is done separated with rolling system. Guidance material is related to library service, information technology in library, increasing reading interest and certain subject that exploit the library as learning source. Especially for student of first, second and third grade the material guidance that given is 3R that is read, write, and aritmatic which is done after learning hour. Guidance material is served by library manager and if there is needed the teacher can be present according to the material that given